2011
DOI: 10.1055/s-0030-1270943
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between Sequential Organ Failure Assessment Score (SOFA) and Cardiac Surgery Score (CASUS) for Mortality Prediction after Cardiac Surgery

Abstract: Both CASUS and SOFA are reliable mortality prediction tools after cardiac surgery. However, CASUS was more accurate in predicting the individual patient's risk of mortality. Thus, use of the CASUS in cardiac surgery intensive care units is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
1
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 12 publications
(15 reference statements)
1
27
1
3
Order By: Relevance
“…Various investigations have identified a clear relationship between organ dysfunction and mortality [24], [25]. In our patients, an elevated SOFA score was associated with unfavorable outcomes.…”
Section: Discussionsupporting
confidence: 47%
“…Various investigations have identified a clear relationship between organ dysfunction and mortality [24], [25]. In our patients, an elevated SOFA score was associated with unfavorable outcomes.…”
Section: Discussionsupporting
confidence: 47%
“…Although these scoring systems were not designed for the specific features of open heart surgery, and they had excluded these patients from their initial development studies, the main and most commonly used scoring systems in the field of intensive care, such as the APACHE II, SAPS II, and SOFA, have been evaluated in this specific subset of patients. 1,3,9,[16][17][18][19][20] In our sample, SOFA exhibited the least satisfactory performance in relation to the prediction of 30-day mortality, something not unforeseen, because the model was originally designed over time to describe the changing severity in the process of organ failure in ICU patients with sepsis 12 ; thus, it was designated more as an indicator of morbidity. In 2003, Ceriani et al 18 examined the use of SOFA scores to predict postoperative morbidity in cardiac surgery patients.…”
Section: Operationmentioning
confidence: 99%
“…This was confirmed by a UK study, which also demonstrated the ICNARC model was a significantly superior predictor of outcome and performed in line with EuroSCORE‐2, the widely used pre‐operative risk‐prediction scoring system . Other studies from Canada and Germany have evaluated alternative postoperative cardiac surgery predictive scores, however their validation is limited by the smaller selection of variables and the fact they are based on data analysis from a single centre .…”
Section: Whose Outcome Is It Anyway?mentioning
confidence: 66%